2020
DOI: 10.1111/ijac.13469
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and phase transition of tobermorite synthesized by hydrothermal reaction from dicalcium silicate

Abstract: In this paper, tobermorite was hydrothermally synthesized from the dicalcium silicate (C 2 S) in sodium silicate solution, and the crystallization and phase transition process were investigated in detail using XRD, Raman spectra, and SEM. The tobermorite is difficult to synthesize when the temperature is lower than 160°C because it gets converted into xonotlite (without Na 2 O) or pectolite (with Na 2 O) when the temperature is higher than 180°C. The crystallization process of tobermorite shows "S" trend with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Typically, tobermorite is synthesized using SiO2-rich materials, such as quartz, silica powder, lime, and silica-rich fly ash [91], [92], [93]. It can be synthesized from dicalcium silicate also [102]. Tobermorite constitutes the primary component of energy-efficient building materials [94], [138], [101].…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…Typically, tobermorite is synthesized using SiO2-rich materials, such as quartz, silica powder, lime, and silica-rich fly ash [91], [92], [93]. It can be synthesized from dicalcium silicate also [102]. Tobermorite constitutes the primary component of energy-efficient building materials [94], [138], [101].…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 99%
“…Sodium hydroxide was roasted with the residue, followed by leaching and filtrating. Silicate could react with sodium hydroxide, while iron compounds did not react with sodium hydroxide [21,22]. The filtrate (liquor 5) contains sodium silicate.…”
Section: Preparation Of Silica and Iron Concentrate From The Residuementioning
confidence: 99%
“…28,33 Research exploring tobermorite synthesis from calcium silicates and calcium aluminum silicates has demonstrated that alkaline solutions are required for precipitation. 16,17,34,35 Sodium bases, such as NaOH, have been shown to facilitate the precipitation of tobermorite better than other alkali metals. 17,35 Tobermorite precipitation from calcium silicates has also been described as the crystallization of CSH gel.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Research exploring tobermorite synthesis from calcium silicates and calcium aluminum silicates has demonstrated that alkaline solutions are required for precipitation. ,,, Sodium bases, such as NaOH, have been shown to facilitate the precipitation of tobermorite better than other alkali metals. , Tobermorite precipitation from calcium silicates has also been described as the crystallization of CSH gel. , The formation of tobermorite and other CCSH phases from pseudowollastonite has been shown to increase when exposed to both sodium and CO 2 ; CCSH phases have precipitated when the carbon is delivered as a salt, for example, as Na 2 CO 3 or NaHCO 3 or CO 2 gas and NaOH. However, the effects of CO 2 and sodium concentrations on the amount and phases of precipitated CCSH have not been explored in detail. Prior work in our laboratory suggested that the crystal structure and dissolution characteristics of the parent silicate were a major factor impacting CCSH precipitation .…”
Section: Introductionmentioning
confidence: 99%